Acurácia do escore pediátrico de alerta no rastreio da sepse - Souza, Mariana Magalhães de Cerqueira (2023)
Introduction: Sepsis in the pediatric age group still represents a major challenge, as this population may have unusual signs and symptoms and better compensatory mechanisms than the adult population. The unfavorable outcome of sepsis cases is usually associated with early failure to recognize signs of clinical worsening, delay in diagnosis and treatment. In this perspective, the Brazilian society of pediatrics advises that health professionals pay attention to the initial signs of sepsis to carry out an immediate and resolute approach. Therefore, pediatric early warning scores of clinical deteriorations can be useful in screening for sepsis cases in hospitalized children and adolescents. Objective: Evaluate the performance of the Pediatric Alert Score (PAS) in the screening of sepsis cases in a hospital context. Method: Retrospective diagnostic test study, based on STARD recommendations. The sample consisted of 190 children and adolescents admitted to a large hospital in the interior of Bahia, Brazil. Secondary data collection was performed in the database of an umbrella research project and in the hospital's charts and records system. Processing and analysis were performed using SPSS® version 25.0 for Windows and MedCalc® version 20.00. PAS performance in sepsis screening was measured using Sensitivity, Specificity, Predictive Values, ​​and Receiver Operating Characteristic Curve (ROC curve) indicators. Results: Among the children and adolescents in the sample, 53,2% were male, 70,5% were black and brown, 64,2% were younger than 5 years old, with a mean age of 4,39 years (DS: 4,28) and the median 3 years (IQR: 1 – 8). About clinical characteristics, 30,5% reported having some comorbidity, 40% were hospitalized due to a diagnosis of infection, the mean length of stay was 12 days (DS: 20,9) and the median was 4 days (IQR: 2 – 13,2). According to the PAS classification, 15,8% had moderate signs and 7,4% had severe signs of clinical deterioration. The prevalence of sepsis in the sample was 10%. The sensitivity, specificity, and positive predictive value and negative predictive value of PAS in sepsis screening were 73,7%, 82,5%, 31,8% and 96,6%, respectively. The area under the ROC Curve was 0,794. Conclusion: The study presents the first evidence on the performance of PAS in sepsis screening in a Brazilian hospital context, being considered a PEWS with good capacity to correctly discriminate pediatric patients with and without sepsis in the studied sample. Bibliographic production: Manuscript entitled “Performance of the Pediatric Alert Score (PAS) in sepsis screening in a Brazilian hospital context”. Technical production: Protocol for the application of the PAS in sepsis screening in inpatient units.